Successful outcome in a twin pregnancy with hereditary motor and sensory neuropathy type -II complicated with heart disease and preclampsia superimposed on chronic hypertension - Debasmita Mondal (Al Ameen Medical College, 2008)
Heridetary motor and sensory neuropathy (HMSN TYPE-2) reflects reduction in the number of primary motor and sensory neurons. The occurrence of this disease is rare in pregnancy but may be exaggerated in pregnancy leading to preeclampsia / eclampsia. Here is a 28 years old 2nd gravidae with twin pregnancy at 31 weeks hospitalized with HMSN TYPE-2 disease and was managed successfully with good feto maternal outcome